CO2 Sequestration in a Carbonate Saline Aquifer: An Investigation into the Roles of Natural Fractures and Well Placement - Abdulrahim K. Al Mulhim; Mojdeh Delshad; Kamy Sepehrnoori (Energies)
CO2 sequestration is considered one of the main pillars in achieving the ongoing decarbonization efforts. A myriad of CO2 sequestration projects targeted sandstone reservoirs since carbonate reservoirs appeared to be unpropitious due to their geological complexity and unfavorable mineralogy and properties. This study investigates CO2 sequestration potential in a carbonate saline aquifer while considering various geological complexities by capitalizing on numerical simulation. A synthetic anticline reservoir model examined the optimum well location and landing zone for CO2 sequestration. Additionally, the model evaluated the role of natural fractures in the migration path of CO2 plume and geochemical reactions throughout the storage process. The study demonstrates that placing the injection well away from the top of the structure in a low-dip region while injecting in the bottom interval would yield the optimum design. After applying a plethora of analyses, geological complexity could impede the migration path of CO2 but eventually produce a similar path when injected in a similar region. The geochemical interactions between the injected CO2 and reservoir fluids and minerals reduce the free and trapped CO2 quantities by dissolving calcite and precipitating dolomite. Furthermore, natural fractures impact the CO2 quantities during early times only when the fractures cross the top layers. Similarly, the CO2 migration differs due to the higher permeability within the fractures, resulting in slightly different CO2 plumes. Consequently, the role of natural fractures should be limited in carbon storage projects, specifically if they do not cross the top of the reservoir. This study reflects a unique perspective on sequestering CO2 while capturing the roles of natural fractures and well placement in depicting the migration path of the CO2 plume. A similar systematic workflow and holistic approach can be utilized to optimize the subsurface storage process for potential formations.